2023
DOI: 10.3389/fimmu.2023.1155478
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis resistance of small airway epithelium is involved in the progression of chronic obstructive pulmonary disease

Abstract: BackgroundAnoikis resistance is recognized as a crucial step in the metastasis of cancer cells. Most epithelial tumors are distinguished by the ability of epithelial cells to abscond anoikis when detached from the extracellular matrix. However, no study has investigated the involvement of anoikis in the small airway epithelium (SAE) of chronic obstructive pulmonary disease (COPD).MethodsAnoikis-related genes (ANRGs) exhibiting differential expression in COPD were identified using microarray datasets obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…The mechanism of drug resistance to anoikis is a prerequisite for tumor metastasis [ 43 ]. Studies have shown that overexpression of CEACAM6 induces anoikis resistance for the reason that CEACAM6 plays a critical role in ECM-cell adhesion process [ 44 46 ]. A majority of CEACAM6 on the surfaces of cancer cells can interact with other members of the CEA family on the surface of cancer cells in an interaction called cross-linking [ 47 ], which results in a significant increase in c-Src kinase activity and caveolin-1 phosphorylation.…”
Section: Ceacam6 and Anoikismentioning
confidence: 99%
“…The mechanism of drug resistance to anoikis is a prerequisite for tumor metastasis [ 43 ]. Studies have shown that overexpression of CEACAM6 induces anoikis resistance for the reason that CEACAM6 plays a critical role in ECM-cell adhesion process [ 44 46 ]. A majority of CEACAM6 on the surfaces of cancer cells can interact with other members of the CEA family on the surface of cancer cells in an interaction called cross-linking [ 47 ], which results in a significant increase in c-Src kinase activity and caveolin-1 phosphorylation.…”
Section: Ceacam6 and Anoikismentioning
confidence: 99%
“…With 10% of the global population affected, COPD is a significant public health problem [ 3 ]. In accordance with the World Health Organization, COPD-related deaths are rising consistently, even predicted to become the third leading cause of death worldwide by 2030 [ 4 ]. Comprehensive transcriptome analysis and genome-wide association studies (GWAS) using integrated mouse models or large human lung tissue datasets have provided a greater understanding of the mechanisms underlying the pathogenesis of COPD in previous research [ 5 9 ].…”
Section: Introductionmentioning
confidence: 97%
“…Besides, gene correlation networks have been widely constructed to extensively understand the mechanism underlying the high-throughput sequencing data [3]. Weighted gene coexpression network analysis (WGCNA) was a common gene correlation analysis method [4], which supplied complete interpretation into the detail of molecular interactions [5][6][7][8]. In this study, RNA sequencing datasets referred to kidney IRI were collected from the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%